SILENTIUM DAN PATHOS ALLAH DI HADAPAN PENDERITAAN MANUSIA (Perspektif Teologis Jurgen Moltmann) - Johanes Jeramu (Lumen Veritatis: Jurnal Filsafat dan Teologi, 2021)
The Covid-19 creates global fear, anxiety and suffering for all humanity today. This global pandemic has become a killer monster that has claimed the lives of many people. In the midst of this tragic situation, the man asks question and doubt about the God's omnipotence and goodness. How could God allow that to happen? If God is all-kind, why is He still silence and apathetic in front of the suffering of the mankind? Where is God when millions of people have died cause of the corona virus? If God is omnipotent, why is He unable to save humanity from this global pandemic? Jurgen Moltmann is a modern theologian who has a brilliant theological view on how to interpret suffering from the perspective of Christian faith. One of his well-known thoughts is the Theology of Hope. Moltmann emphasized that God promise to do something for the future is more important than what he has done in the past. The suffering of the present can only be understood and transformed with a Hope for the future. Only in the perspective of eschatological hope that we can find the meaning and value behind the reality of suffering today.